Inverse Cherenkov dielectric laser accelerator with alternating phase focusing for subrelativistic particles - Liwen Zhang; Hongliang Xu; Weihao Liu (Physical Review Accelerators and Beams)
In this paper, we propose a dielectric laser acceleration scheme based on the inverse Cherenkov effect, which uses the principle of alternating phase focusing to accelerate, confine, and bunch the subrelativistic electron beam over an extended distance. In this scheme, the reference electron is always synchronized with the acceleration wave and is thus continuously accelerated. Electrons around it are alternately subjected to focusing and defocusing forces by alternately jumping its phase. Optimizing the focusing period can achieve stable beam confinement. Simulations show that a 100 keV electron bunch can be coherently accelerated with the average acceleration gradient of 220.8  MV/m, and it can travel nearly 200  μm without loss in a channel only 500 nm wide. This approach is scalable, potentially enabling the development of millimeter-scale MeV particle accelerators for ground-breaking use in medical, scientific, and materials research.